Green ultrasound-assisted extraction of astaxanthin from fermented rebon shrimp (cincalok) using vegetable oils as solvents☆ - Prayitno Dwi Imam; Dewi Eko Nurcahya; Pringgenies Delianis; Brotosudarmo Tatas Hardo Panintingjati (Oilseeds and fats, crops and lipids, 2022)
Cincalok is a typical food from West Kalimantan made from fermented rebon shrimp containing astaxanthin, the most potent antioxidant in nature. This study investigated an efficient method for extracting astaxanthin from the cincalok using vegetable oils as solvents. Olive, sesame, grape seeds, coconut, and virgin coconut oil were used as alternative solvents. The effect of various parameters on extraction yield was also studied. N-hexane and acetone were also used for comparison. Amplitude level and extraction time were the factors investigated concerning extraction yield. Comparative studies between traditional extraction methods and extraction assisted by ultrasonication have also been carried out. The astaxanthin content as total carotenoids in oil extract was analyzed using a UV-vis spectrophotometer with a standard external method. The optimum ultrasound-assisted extraction condition of astaxanthin from cincalok was 40% amplitude for 3  minutes, with 100.62  μg/g of astaxanthin extraction yield when used virgin coconut oil as a solvent. In this way, oils enriched with astaxanthin are produced.